VARIASI PILIHAN BAHASA SANTRI WANITA DI MADRASAH TAKHASHUSHIYYAH DALAM INTERAKSI SOSIAL DI PESANTREN - Rusbiyantoro, Wenni; Susylowati, Eka (PRASASTI: Journal of Linguistics, 2021)
The variety of language used by speakers in the Assalaam Modern islamic Boarding School and Al-Mukmin Ngruki Islamic Boarding School in Indonesia. The purpose of the study is to identify variations of language choice in the domain of friendship, education, religion, and work. The results showed that Indonesia is more dominant in the domain of friendship, education, religion, and work. Javanese is used in the domain of friendship, meanwhile English is used in the domain of education and friendship. Arabic is used in the domain of frindship, education, and religion. There are three types of language variations, namely single language variation, code switching, and code mixing.